Kinetic Condensation in The performance of the Iraqi theatrical actor - The play Ahriman as A model - Ali Majeed Jassim; Mohammad Ali Ibrahim Al-Asadi; Star Dakhil Sayfi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The actor's performance in his live presence on the stage has occupied all those working in it, in addition to many academic and critical studies, and it is still the first and last element/axis in supporting the stage, with the pulse of life and the launch of sound and movement in every place and corner in it; and in order for this life to continue in its continuity, it has undergone a lot of deletion, addition, change and reduction as well, to appear with a complete appearance of elegance and beauty, towards an audience that seeks that, so the kinetic and gestural condensation formed an aspect of that beauty, by removing everything that is superfluous and unnecessary in order to create a clear and simple change, far from complexity and ambiguity, so that the theatrical image formed on the stage is extremely beautiful and clear to the recipient.